Circular - Schevenels, Walther, b. 1894
011-0095-001 Federation Syndicale Internationale International Federation of Trade Unions Internationaler Gewerkschaftsbund 9, AVENUE D'ORSAY, PARIS-VIIe ADRESSE TELEGRAPHIQUE : TELEGRAPHIC ADDRESS : TELEGRAMMADRESSE : INTERFED. PARIS TELEPHONE : INVALIDES 45-88 Sch/H/B. Sit. Espagne 176 26th April, 1937. To Affiliated National Centres. Dear Comrades, We would remind you that the last joint conference of the IFTU and LSI, held in London on the 10th and 11th March, 1937, decided to organise a propaganda week for Spain, as far as possible simultaneously in all countries. In agreement with Comrade Adler, General Secretary of the LSI, we have, on behalf of the IFTU Executive, issued the May Day Manifesto for this year with particular reference to solidarity for Spain. While in Spain, from whence we returned this morning, we noted, during the many contacts which we had with the various organisations of the workers, how much value our Spanish comrades attach to these May Day demonstrations, to which we have given the significance indicated above. We would therefore again urge that, as far as possible, the May Day manifestations held in the capitals and principal towns of all countries should emphasise very markedly our solidarity with Spain, and that propaganda for Spain be continued for a week following the 1st May, as was decided in principle by the London Conference. We should be very glad to have as complete an account as possible of the demonstrations organised with your collaboration in your country. Thanking you in advance, Yours sincerely, W. Schevenels General Secretary. 292/946/11/95